2008
DOI: 10.1557/jmr.2008.0036
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration behavior of the Cu/Au/SnAgCu/Cu solder combination

Abstract: The electromigration behavior of the Cu/Au/SnAgCu/Cu combination was investigated under 103 A/cm2 of current stressing at ambient temperature. The Au layer, when it acts as a cathode, was consumed continuously, and no significant compound was found at the interface. Meanwhile, Cu6Sn5 was formed at the anodic Cu layer, and the thickness of the compound increased with increasing time. The Au atoms were found to be trapped in Cu6Sn5 within the solder matrix. The AuSn4 compound precipitated while attaching to Cu6S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…6(b) tells that interfacial AuSn 4 was only observed for the current stressing specimen. The migration of Sn from the solder toward the anode upon current stressing was a reasonable explanation in our previous study [11]. According to Eq.…”
Section: 2supporting
confidence: 75%
See 3 more Smart Citations
“…6(b) tells that interfacial AuSn 4 was only observed for the current stressing specimen. The migration of Sn from the solder toward the anode upon current stressing was a reasonable explanation in our previous study [11]. According to Eq.…”
Section: 2supporting
confidence: 75%
“…This occurrence implies an insignificant effect of chemical potential, and thus the parameter of J CP in Eq. (11) for Cu can be neglected; only J EM was considered for the consumption of Cu under current stressing. As a result, the total flux of Cu was approximately equal to that induced by EM (J total Cu z J EM Cu ).…”
Section: Kinetics Of Cathodic Reactions Under Current Stressingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Chiu and Lin reported that the Au layer was consumed continuously in the Au/Sn-Ag-Cu/Cu solder combination when the electrons traveled from the Au side to the Cu side, and no microstructure evolution was found in the reverse direction of electron flow. 13 Other researchers also found that current-crowdinginduced electromigration failure would happen at the Cu side with electrons flowing from the Cu side to the Ni side, while the joint with electrons flowing from the Ni side to the Cu side survived the current stressing. [8][9][10][11] Chen and coworkers 14,15 investigated the electromigration effect upon the Sn/Cu, Sn/Ni, and Ni/Zn interfacial reactions and found the passage of electric current only had notable effect upon the Sn/Ni interfacial reactions.…”
Section: Introductionmentioning
confidence: 96%